(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The differences in the characteristics of male and female consumers also cause differences in purchasing decision making. Before buying products and services, female consumers will collect subjective information from the people around them, while male consumers prefer objective information based on the quality of the products and services. In addition, female consumers have a higher acceptance of risk when compared to male consumers. Therefore, female consumers are more careful in making purchases. Because of these differences in characteristics, this study aims to determine whether there are differences in adopting self ordering machines at fast food restaurants based on Theory of Acceptance and Use of Technology (UTAUT). Self Ordering Machine is a technological innovation in the company’s business process that allows customers to order and pay for orders independently. With the implementation of the Self Ordering Machine, it is hoped that the company can improve its performance. The results showed that there were no differences between male and female consumers in adopting the Self Ordering Machine.